Dictions Used by Religious Leaders in The Diffusion of Extension Forestry Program in Probolinggo Municipal - Tirmidi, Tirmidi (Universitas Nurul Jadid, 2019)
An element identified as one of key points in the success of diffusion of extension forestry program, namely greening up to 6.000 hectares, was the involvement of religious leaders, especially on communicating the program to the villagers. This paper aims to describe, analyze, and interpret the dictions used by religious leaders in the program. Through a qualitative research designed in phenomenological approach, especially at naturalistic paradigm, the research found that instead of using that of semantically classified as environmental and social terms, the religous leaders preferred using that of economical terms, namely financial benefits of planting trees for the local farmers. A proposition filed from this research is: communication of innovation in the field of extention forestry program will be accepted widely and quickly by villagers when the dictions used are words that emphasize on financial benefits which might be obtained from the program.